2015
DOI: 10.4236/cm.2015.61006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Analysis of a Cerebellar Watershed Infarction

Abstract: Objective: To investigate the characteristics of vascular lesions in patients with a cerebellar watershed infarction. Methods: Clinical data from 178 cases of cerebellar infarction were collected with magnetic resonance imaging (MRI) scan results, including diffusion weighted imaging (DWI), a magnetic resonance angiography (MRA), and computed tomography angiography (CTA). The cases were divided into cerebellar watershed and non-watershed infarctions based on lesion location, which was revealed by DWI. Forty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Cerebellar watershed infarcts remain less well-described, with scattered case reports and case series describing predominantly embolic watershed infarcts in adults. [3][4][5][6] A few authors have emphasized the distinction between superficial cerebellar borderzone embolic infarcts and deep cerebellar watershed infarcts, the latter related to hypoperfusion and centered at the interface between the penetrating arteries of the cerebellar arteries. [7][8][9][10] Although some authors have asserted that deep watershed infarcts predominantly affect the deep cerebellar white matter, several lines of evidence suggest that focal injury to the gray matter at the depth of the cerebellar fissures is, in fact, the expected pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar watershed infarcts remain less well-described, with scattered case reports and case series describing predominantly embolic watershed infarcts in adults. [3][4][5][6] A few authors have emphasized the distinction between superficial cerebellar borderzone embolic infarcts and deep cerebellar watershed infarcts, the latter related to hypoperfusion and centered at the interface between the penetrating arteries of the cerebellar arteries. [7][8][9][10] Although some authors have asserted that deep watershed infarcts predominantly affect the deep cerebellar white matter, several lines of evidence suggest that focal injury to the gray matter at the depth of the cerebellar fissures is, in fact, the expected pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The patient presented herein developed multiple cerebral border zone infarcts after aggressive but carefully monitored treatment of blood pressure with labetalol and nitroprusside. Several modern imaging studies suggest that an internal watershed infarction is primarily caused by hypoperfusion as seen in our patient; this should not be confused with cortical watershed infarct, which is primarily caused by microembolism[ 30 - 33 ].…”
Section: Discussionmentioning
confidence: 76%
“… 10 The authors reported that hemodynamic abnormalities caused by vascular lesions may decrease cerebral perfusion pressure, and may lead to accumulation of microemboli in the vascular periphery, leading to infarction in watershed area of supplying cerebral vessels. 10 The authors proposed that patients with cortical watershed infarctions have high prevalence of stenosis in major blood vessels, and an examination of extracranial vessels especially the extracranial segment of the vertebral artery must be performed so that an early intervention and further progression of stroke can be prevented. 10 However in our patient there was no evidence of any cerebral vessels anatomic variation and neither any episode of documented intra-operative hypotension was present.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The authors proposed that patients with cortical watershed infarctions have high prevalence of stenosis in major blood vessels, and an examination of extracranial vessels especially the extracranial segment of the vertebral artery must be performed so that an early intervention and further progression of stroke can be prevented. 10 However in our patient there was no evidence of any cerebral vessels anatomic variation and neither any episode of documented intra-operative hypotension was present. We can only hypothesize that cerebellar stroke may have been caused due to combination of factors like patent foramen ovale, co-existing vascular disease (non-visualization of bilateral vertebral and proximal portion of basilar artery) combined with un-noticed blood pressure oscillations during spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%